PRAGMATIC TREND IN STYLISTICS - Ashurova, Dilyaram (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2023)
The article discusses the problems of stylistics from the pragmalinguistic perspective. Stylistics and Pragmalinguistics, as the analysis proves, have common ground in many respects: the problem of intentionality and pragmatic intentions, the theory of perception and impact on the addressee, the conception of linguistic personality, the categories of implicitness and context determinism, and pragmatic effectiveness of language functioning. The main findings of the research are a) close links between Stylistics and Pragmalinguistics; b) the expediency and effectiveness of applying some principles of communicative pragmatic analysis to stylistic studies c) the necessity of allocating the pragmatic trend to Stylistics of fiction under the name Pragmastylistics.